What can we know about the future? Epistemology and the credibility of claims about the world ahead. Issue 1 (16th August 2021) - Clardy, Alan
Abstract : Purpose: The purpose of this paper is to examine whether the results of futures studies are knowledge or if not, what it is that futures studies actually produce. Five types of representations of the future are the result of these studies. As the value of futures studies depends on no small measure of their credibility, the standards for carrying out and reporting these studies are identified along with a description of how Toulmin's model of informal logic can be used to best improve their credibility. Design/methodology/approach: This paper is based on a multi-disciplinary literature review and integrative analysis. Findings: Using epistemological criteria for knowledge as truth, belief and rationale, the results of futures studies are not and cannot be knowledge. Instead, futures studies produce five kinds of "representations of the future": predictions, projections and forecasts, scenarios, visions and structures for action. Six standards for conducting and reporting the results of futures studies are provided which will increase the credibility of these studies. Toulmin's informal logic format will provide the foundation for the most persuasive basis of such studies. Practical implications: Futurists will understand that the products of their studies are not knowledge and why this is the case. They will also understand that the type of futures studies they are conducting are either conditional, contingent propositions or normative prescriptions in nature. There are six guidelines for carrying out and reporting futures studies which can also be used to assess the quality of published studies. They will see how the use of a certain kind of informal logic can establish the most credible foundations for their studies. Originality/value: As an integrative literature review, it incorporates and simplifies widely disparate existing contributions to the topic of the nature of knowledge regarding futures studies and the criteria for making such studies as credible as possible.